2012
DOI: 10.1590/s1726-46342012000300007
|View full text |Cite
|
Sign up to set email alerts
|

Precisión de la taquipnea y las retracciones subcostales como signos clínicos para diagnóstico de neumonía adquirida en la comunidad en niños: revisión sistemática y metaanálisis

Abstract: Objetivos. Evaluar si la taquipnea y las retracciones subcostales son predictoras eficientes para el diagnóstico de neumonía adquirida en la comunidad (NAC) en niños. Materiales y métodos. Se revisaron las bases de datos: PubMed, LILACS, The African Journal Database y The Cochrane Central Library. Se incluyeron estudios originales que evaluaron el rendimiento diagnóstico de los criterios clínicos de taquipnea o retracciones subcostales, definidos según los criterios de la Organización Mundial de la Salud (OMS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…In this study it was observed that the kappa index showed statistical significance (p value < 0.05) for the presence of at least a reasonable correlation in all segments of cephalic vein (renal or non renal) for segment adequacy by ultrasound criteria, the gold standard of evaluation, pointing to the value of this maneuver in physical examination. Since there is no similar description in the literature on the ability of venous percussion to diagnose an adequate superficial venous segment of upper limbs suitable for venous puncture or for arteriovenous fistula construction, a comparison of the results found in this study with previous studies of clinical signs in different clinical situations[2532], found that the indices regarding traditional physical examinations techniques such as pulmonary auscultation were inferior to the ones found in this study[25]. This provides evidence for including venous percussion in a traditional physical examination, as part of the triage done during physical examination, and, maybe with further studies, on already existing scales for difficult venous access [3,33].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In this study it was observed that the kappa index showed statistical significance (p value < 0.05) for the presence of at least a reasonable correlation in all segments of cephalic vein (renal or non renal) for segment adequacy by ultrasound criteria, the gold standard of evaluation, pointing to the value of this maneuver in physical examination. Since there is no similar description in the literature on the ability of venous percussion to diagnose an adequate superficial venous segment of upper limbs suitable for venous puncture or for arteriovenous fistula construction, a comparison of the results found in this study with previous studies of clinical signs in different clinical situations[2532], found that the indices regarding traditional physical examinations techniques such as pulmonary auscultation were inferior to the ones found in this study[25]. This provides evidence for including venous percussion in a traditional physical examination, as part of the triage done during physical examination, and, maybe with further studies, on already existing scales for difficult venous access [3,33].…”
Section: Discussionmentioning
confidence: 86%
“…Analysis of the sensitivity, specificity and diagnostic accuracy of a clinical sign in a structured and systematic way enables identification of possible forms of assisting diagnosis of clinical conditions in a simple manner. From the point of view of public health, this can have a real impact on the logistics of diagnosis on remote areas of undeveloped countries as has been demonstrated in cases of community-acquired pneumonia in children[29,30,32].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of coughing and tachypnea, mainly among patients with previous history of wheezing, was not pathognomonic of pneumonia. 16 However, the association of tachypnea, SCS 17 and NF 18 increased the chances of CAP diagnosis, especially if the patient presented coughing and fever. The presence of SCS in more than half of the cases evaluated illustrates the severity of the clinical framework in the diagnosis of children attended in the emergency research service.…”
Section: Discussionmentioning
confidence: 99%
“…A nivel local no se han realizado estudios que describan la realidad epidemiológica, por eso es necesaria la investigación sobre esta patología. Se estima que cada año, 150 millones de niños y niñas desarrollan la enfermedad y 11 millones de niños son hospitalizados a causa de neumonía y casi todos ellos viven en países en vías de desarrollo; por cada niño que pierde la vida a causa de neumonía en un país desarrollado, más de 2.000 mueren en un país en vías de desarrollo [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionunclassified